HOW DO DOMESTIC TOURISTS, UNEMPLOYMENT RATE, AND EXPORT VALUES AFFECT GROSS REGIONAL DOMESTIC INCOME FACING COVID-19? - Rachmawatie, Dessy; Purnomo, EkoPriyo; Fitria, Anita; Fathani, Aqil Teguh (The journal of contemporary issues in business and government, 2021)
The purpose of this study is to examine the impact of the number of domestic tourists, the unemployment rate, the value of exports, and cases of COVID-19 on the gross regional domestic product (GRDP)in DKI Jakarta during the face of COVID-19. The researchers used secondary data analysis and reviewed relevant literature studies. This study applied quantitative methods and used secondary data. The data wereobtained from the websites of the DKI Jakarta Central Statistics Agency and the DKI Jakarta COVID-19 Task Force. The data obtained were time-series data types in 2019-2020. Data analysis employed EViews9, anddata were analyzed utilizing a regression estimation model of time series with a quantitative approach. The results showed that during COVID-19, domestic tourist visits had a positive and insignificant effect on GRDP with a probability value of 0.2286. The unemployment rate and COVID-19 cases had a significant negative effect on GRDP with a probability value of -0.0003 and -0.0143, respectively. Meanwhile, exports had a significant positive effect on GRDP with a probability value of 0.0049. Besides, this research paper highlights an empirical analysis based on real data of tourism and socio-economics in DKI Jakarta.